2014
DOI: 10.1111/cea.12326
|View full text |Cite
|
Sign up to set email alerts
|

IgE antibodies to alpha‐gal in the general adult population: relationship with tick bites, atopy, and cat ownership

Abstract: The prevalence of alpha-gal sIgE antibodies in these general adult European populations is similarly low. The presence of alpha-gal sIgE antibodies is associated with a history of tick bites, atopy, and cat ownership.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
87
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(102 citation statements)
references
References 33 publications
12
87
0
3
Order By: Relevance
“…This was also noted in a recent study among 2,297 Danish and 444 Spanish randomly selected adults who showed a frequency of α-Gal IgE of 5.5 and 8.1%, respectively [10]. Interestingly, the authors concluded that presence of α-Gal IgE antibodies is associated with a history of tick bites, atopy and cat ownership.…”
Section: Discussionsupporting
confidence: 55%
“…This was also noted in a recent study among 2,297 Danish and 444 Spanish randomly selected adults who showed a frequency of α-Gal IgE of 5.5 and 8.1%, respectively [10]. Interestingly, the authors concluded that presence of α-Gal IgE antibodies is associated with a history of tick bites, atopy and cat ownership.…”
Section: Discussionsupporting
confidence: 55%
“…A total of 3,405 were eligible for invitation (21 had emigrated and 45 had died). A total of 2,308 (45.8% men) agreed to participate and were re-examined between November 2011 and November 2012 [7]. The median age was 55.7 (range 24-76) years.…”
Section: Methodsmentioning
confidence: 99%
“…In Europe, Ixodes ricinus has been implicated while in Australia the relevant tick is Ixodes holocyclus [1719]. In fact, there are now reports of delayed anaphylaxis to red meat in Australia [15,20], France [21,22], Germany [23,24], Sweden [25], Spain [26•], Japan [27], Korea [28] and Belgium [29]. Notably, in each of these countries there is evidence that tick bites are the primary cause of the sensitization [19••] and that the primary or sole sensitization is to alpha-gal.…”
Section: Tick Bites and The Development Of Ige Ab To Alpha-galmentioning
confidence: 99%